2008
DOI: 10.1007/s11701-007-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Can robotic assisted laparoscopic prostatectomy be recommended to obese patients?

Abstract: Experienced robotic surgeons report lower estimated blood loss (EBL) and transfusion rates with similar clinical outcomes for robotic assisted laparoscopic radical prostatectomy (RALP) compared to open radical retropubic prostatectomy (RRP). We reviewed our experience with RALP to investigate how to counsel overweight and obese patients being considered for RALP regarding risk of major perioperative complications, oncological outcomes, and short-term recovery. We reviewed the data on 1,513 patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Although the link between obesity and aggressive disease, and thereby PSM, should apply to RALP too, it is less clear whether obesity is a risk factor for PSMs in RALP. Most prior studies found no link, although these studies were limited by small sample sizes 20 . Consistent with prior studies, we also found no association between obesity and PSMs in RALP, suggesting the potential advantages of the robotic technique might be technically favorable for obese men.…”
Section: Discussionsupporting
confidence: 87%
“…Although the link between obesity and aggressive disease, and thereby PSM, should apply to RALP too, it is less clear whether obesity is a risk factor for PSMs in RALP. Most prior studies found no link, although these studies were limited by small sample sizes 20 . Consistent with prior studies, we also found no association between obesity and PSMs in RALP, suggesting the potential advantages of the robotic technique might be technically favorable for obese men.…”
Section: Discussionsupporting
confidence: 87%
“…There was no difference in lymph node yield. The median (range) number of lymph nodes was 5 (2-21) and 5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) in the 2 groups (BMI > 40 kg/m 2 , and BMI < 40 kg/m 2 ) respectively. While the morbidly obese had a higher rate of harboring more aggressive disease on final pathology than the non-morbidly obese group (pT3 rates 27.5% vs. 7.5 % respectively, p=0.04), there were no significant differences in other postoperative…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between higher BMI and increased aggressiveness of tumours, as well as the heightened risk of biochemical recurrence following radical prostatectomy (RP), has been well documented [ 27 ]. Furthermore, obesity poses additional challenges during RP, particularly in surgeries utilizing robotic assistance, potentially impacting oncological outcomes by increasing the complexity of the procedure, extending operative times, and elevating the likelihood of converting to open surgery [ 28 ]. Given that over 70% of men eligible for RP fall into the overweight or obese categories, this presents a significant concern for surgical management and outcome optimization [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%